Исследование пиролиза газовых конденсатов месторождений Томской области - Смольянинов С. И. Станислав Иванович; Кравцов А. В. Анатолий Васильевич; Кузнецова В. А.; Медведев М. Д. (1976, 1976)
Заглавие с титульного листа